The Involvement Of Austin's Ideas In Semantics - Ahmadin, Dimjati (ULUL ALBAB Jurnal Studi Islam, 2004)
There are instructions from the theory of speech acts that in the initial period, there were differences of opinion among experts. Philosophy, just like the difference between Ibnu Sina and Thomas Hobbes, the first time to examine the problem firmly and complete namely research conducted by J.L. Austin (linguist). This library research intends to study whether two prominent writers in the field semantics namely John Lyons in his book "Linguistic Semantics" and Ruth Kempson in his book "Semantic Theory" involves Austin's ideas in discussion they. Based on the data obtained and the discussions that have been carried out, it can be concluded that the two semantic experts involved Austin ideas in their discussion in semantics. However, the way they involve ideas Austin in their discussion varies from one another, ha / this is in line with the development of social sciences which have never been constant including semantics, as mentioned in previous discussions. Furthermore, it can also be concluded that the two semantic experts took advantage of Austin's ideas in their discussion, even though sometimes their opinions are different from Austin.